Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Penggunaan Model Pembelajaran Problem Based Learning (PBL) Pada Mata Pelajaran Ekonomi di SMAN 1 Palembayan - S, Khisnatul Khariyah; Kurniawati, Tri (Jurnal Salingka Nagari, 2024)
This research aims to improve students' critical thinking (CT) skills through the application of the PBL model in economics subjects at SMAN 1 Palembayan. The research was carried out in 2 cycles. Cycle I was in class XI F EKO 1 semester II of the 2023/2024 academic year, while cycle II was carried out in class The tools used are comment sheets to see student and teacher activities, field notes to record things that are not included in the observation sheet, and test questions to determine students' critical thinking abilities using the PBL model. The results of this research are the results of students' CT ability tests in cycle I and cycle II, the results of students' CT ability tests in cycle I were 65.63% with a student classical average of 77.9. Meanwhile, the results of students' CT abilities in cycle II increased to 84.375% with a student classical average of 83.1. Thus it can be concluded that the PBL model can improve students' CT abilities.